Analyzing How Liquidity, Efficiency, and Bank Size Influence Profitability: Ownership Structure as a Moderator - Nulhakim, Lukman; Kristijadi, Emanuel (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Despite asset growth, rural banks in East Java face declining profitability, with limited research on how financial factors and government ownership shape this performance. This study examines the factors influencing the profitability of rural banks (Bank Perekonomian Rakyat/BPR) in East Java, Indonesia, focusing on liquidity, asset quality, operational efficiency, bank size, and government ownership. The research adopts a quantitative explanatory design with a correlational approach, using secondary data from audited financial statements of rural banks registered with the Financial Services Authority (OJK) for the period 2019–2023. The sample was selected through purposive sampling, covering rural banks with available financial reports and a minimum asset size of IDR 50 billion. Data were analyzed using multiple regression analysis (MRA) to test the direct effects of financial variables on profitability and the moderating role of regency government ownership. The results show that operational efficiency, measured by the Operational Expense to Operating Income ratio (BOPO), negatively affects profitability, highlighting the importance of cost management. Liquidity, as indicated by the Cash Ratio (CR), and asset quality, reflected by the Non-Performing Loan (NPL) ratio, have an insignificant impact on profitability in this context. Regency government ownership moderates the relationship between operational efficiency and profitability, suggesting that local government ownership can reduce the adverse effects of high operational costs. However, local government ownership did not significantly affect asset quality, bank size, or profitability. This study underscores the need for better operational efficiency in rural banks.